Enrichment of Chromium(III) from Tannery Sludge in the Presence of Calcium - Cetin, Gulten; Kocaoba, Sevgi; Akcin, Goksel (Asian Journal of Chemistry, 2013)
In recent years, development of the leather industry and rapid increasing of the centers of leather production has caused to focus on control of the pollution consisting of tannery wastes. The sludges of the leather waste are main sources of the pollution in the leather industry. In this study, removal of chromium and calcium ions from sludges of the leather waste and developing an enrichment method to recover of chromium in the presence of calcium was conducted in the acidic range. The method is based on enrichment of chromium(III) by means of solubility of samples of the sludge with sulphuric acid solution at pH 1 following multi extraction by solutions of the previous extracts. The release behaviour of chromium and calcium ions from the sludges and separation of each other was characterized by using synthetic and real sludges such as biological sludge and pre-treatment output sludge of the wastewater of leather. The amount of the satisfactory enrichment of chromium from sludges has been obtained while significant amount of calcium remains in sludge.